Corporate Social Responsibility: Ketika Berkembang Menjadi Trend Global - Prasetyani, Dwi - (Jurnal Ilmu Ekonomi dan Pembangunan, 2009)
CSR developments from time to time as part of the process of development of a global trend, part of the progress of thinking businesses, a regard for the activities they have already undertaken. Along with the strengthening of the pressures and demands on the impact of corporate activity on social life and the environment led to the company changing its business strategy of a single bottom line profit-seeking to the triple bottom line of the balance of the realm of social-economic-environmental. CSR responsibilities guarantee the continuity of the company as well as social welfare for the surrounding community. Implementation of CSR is seen as an investment for growth and sustainability of the business as a company contribution in addressing social problems that afflict society that is not likely in part due to the activities of the company itself.